Clogging and flow assessment of cohesive soils for EPB tunnelling: Proposed laboratory tests for soil characterisation. (December 2019) - Oliveira, Daniela G.G. de; Thewes, Markus; Diederichs, Mark S.
Abstract: For earth pressure balance (EPB) machines, it is fundamental to characterise the excavated ground in its natural and conditioned states. The characteristics of the excavated material have a direct influence on machine operation, impacting the functions as a support medium maintaining the support pressure ahead of the tunnel face, besides its transportation and disposal. The current available methods to assess the clogging potential focus mainly on sedimentary pure clayey soils, not including mixed soils. Mixed soils exist widely in nature, including a wide variety of residual soils, which are by-products of intense tropical weathering. This paper presents a combined laboratory routine to characterise and evaluate the clogging and fluidity of soils, including mixed soils by considering different clay fractions. This routine still requires tests conducted directly on-site, where the results should be compared with machine operation parameters, such as torque of cutterhead and screw conveyor, temperature, pressure, as well as occurrence of clogging. This testing procedure provides on-site assessment that can also be conducted prior the excavation using borehole material. The intention of this routine is to provide a geological-geotechnical qualitative characterisation of the material to be excavated, and of the effectiveness of the additives that could be added, as a general guidance for EPB soil conditioning, especially of cohesive soils. The advantage of this routine is its simplicity and low cost to be reproducible in different laboratories and jobsites, making feasible the comparison between different soils by different operators, before and during excavation.